Interfacial optimization of g-C3N4-based Z-scheme heterojunction toward synergistic enhancement of solar-driven photocatalytic oxygen evolution - Yang, Xiaofei; Tian, Lin; Zhao, Xiaolong; Tang, Hua; Liu, Qinqin; Li, Guisheng (Applied catalysis. B, Environmental, 2019)
[Display omitted] Tandem Z-scheme Ag3PO4/g-C3N4 heterojunctions were explored as highly efficient photocatalysts for driving oxygen evolution reaction under visible-light irradiation. •A fish scale-like g-C3N4/Ag3PO4 composite photocatalyst was fabricated.•The heterojunction photocatalyst exhibits highly improved oxygen evolution than pristine Ag3PO4.•The improvement in the activity is ascribed to synergistic effects of modified g-C3N4.•Z-scheme configuration is suggested to be responsible for enhanced redox catalytic capability. Exploring active catalyst materials for solar-driven photocatalytic water splitting into oxygen has proven extremely challenging, mostly due to poor oxygen-evolving efficiency originating from intrinsically sluggish oxygen evolution reaction (OER) kinetics. Ag3PO4 has been actively pursued as a promising photocatalyst for oxygen evolution from water-splitting. However, its low OER efficiency is a long standing problem. Both the construction of Z-scheme Ag3PO4-based composite photocatalytic systems and the optimization of surface morphology and interfacial contact in heterojunctions photocatalysts would be beneficial for boosting OER efficiency. Here we report on the fabrication of Ag3PO4/fish scale-like graphitic carbon nitride (g-C3N4) sheet composites with well-defined heterostructures and intimate interfacial contact driven by electrostatic assembly. The Ag3PO4/modified g-C3N4 composites photocatalyst reveals significantly enhanced oxygen-evolving activity under light-emitting diode (LED) illumination. Effective surface modification of g-C3N4, strong interfacial interactions between two semiconductors and tandem Z-scheme-type pathway for more efficient charge transfer synergistically accelerates the redox capability of Ag3PO4 for OER. This work may provide new insights into the design and construction of high-performance solar-driven Z-scheme photocatalytic water splitting systems.